Penguatan Peran Guru di Era Digital Melalui Program Pembelajaran Inspiratif - Adang Sutarman; I Gusti Putu Wardipa; Mahri Mahri (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2019)
This article aims to describe how to strengthen the role of teachers in the digital age through inspirational learning programs. This research uses a qualitative approach with literature study. Data both primary and secondary are collected and then analyzed and presented descriptively. The findings of the analysis reveal that in an effort to strengthen the role of teachers in the digital era through inspirational learning programs, it is more optimal to pay attention to four things: first, to strengthen the cultivation of character through example, habituation, reinforcement, and internalization in the learning process; secondly, creating a classroom management system that empowers through quantum teaching; third, optimizing the process of habituation and literacy development in the classroom and its integration in learning; and fourth, using blended learning methods in learning.